Nano-Indentation Measurement of the Tribo-Layer on Stainless Steel and Brass Surfaces Rubbed against DLC in Water - Michimasa Uchidate (Japanese Society of Tribologists, 2008)
In this paper, in order to clarify the tribology between diamond-like carbon (DLC) and metals under water lubricated conditions, nano-indentation and shear strength measurements for the tribo-layers were attempted in water. Stainless steel (AISI 630) and brass (P31CHL) with the tribo-layer formed by rubbing against the DLC were cut and immersed in the water, and then, the indentation and shear strength measurements were carried out with the Berkovich type indenter and a spherical indenter. The nano-indentation measurement showed that the tribo-layer in the water is a water-absorbing, gel-like product. The shear strength measurement indicated the value between a few MPa and 10 MPa.